Effects of plant row spacing on growth and yield of curry plant (Murraya koenigii) in south-south Nigeria - Agba, Oliver; ADIAHA, MONDAY (SPC Journal of Agricultural Sciences, 2018)
Curry plant (Murraya koenigii) is a herbaceous plant of the Rutaceace family. It is one of the less known under-exploited plant species that lack basic literature information on the cultivation and agronomic techniques, but has high economic importance. The plant shoots; leaves, fruits and roots are use as food, culinary, spices, vegetables, medicinal, cosmetics and other domestic purposes. Thus, studies were conducted to determine the effects of spacing (planting distance) on the growth and yield of Curry plant (Murraya koenigii) in Cross River University of Technology, Obubra, in the Agronomy Teaching and Research Farm, Cross River State South-South, Nigeria. The design of the study was a randomized complete block design (RCBD). Treatments were six spacing (planting distance inter and intra rows respectively. Result indicated that closer spacing of 60 x 30cm, 70 x 50cm significantly reduce number of leaves, branches, dry weight of leaves and stem per plant but gave taller plant height than wide plant spacing of 100 x 100cm and 120 x 100cm in 2015 and 2016 cropping seasons.Curry plant fresh leaf yield per plant was significantly higher in wider row spacing than close row plant spacing. The plant spacing of 120 x100cm produced the highest fresh and dry leaf yield per plant of 79.11g/plant and 6.59g/plant in 2015 and 76.35g/ha and 6.37g/plant in 2016 respectively. On the other hand, the fresh leaf yield on per hectare basis was higher in close row spacing compare with wider row spacing. The highest fresh leaf yield of 0.061 t/ha in (2015) and 0.064 t/ha in 2016 were produced in plots with close spacing of 60 x 30cm. Farmers are encourage to introduce and cultivate Curry plant (Murraya koenigii) into the regular farming system at a spacing of 70 x 50cm and 80 x 60cm for both optimum fresh and dry leaves yield per plant and hectare based on these findings.